Konsep dan Penerapan Intervensi Prehospital pada Stroke: Sebuah Tinjauan Pustaka - Rahmawati, Novia; Pebrianti, Sandra; Nursiswati, Nursiswati (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Stroke patients require immediate medical treatment before 4.5 hours to reduce the risk of death and disability. Stroke patients may experience impaired brain function caused by damage or death of brain tissue. Delay in treating stroke in patients can cause brain damage that appears more severe. Prehospital intervention can be an important initial treatment for stroke patients either while the patient is still at home or during the transfer process to the hospital. This literature review aims to determine the concept and application of prehospital interventions that can be given to stroke patients. This research is a literature review using the Pubmed database and the Google Scholar search engine. The English keywords used “stroke AND prehospital intervention OR emergency medical services OR EMS”. Meanwhile, the Indonesian keywords used “stroke AND intervensi prehospital OR emergency medical services OR EMS”. The results obtained were 19 full-text articles discussing prehospital stroke interventions with the year of publication 2012-2022. In conclusion, the prehospital aspect of stroke in Indonesia still needs development in terms of human resources and infrastructure in order to provide optimal service for patients who have had a stroke. Keywords: Emergency Medical Services, Mobile Stroke Unit, Prehospital, Stroke  ABSTRAK Pasien serangan stroke memerlukan penanganan medis segera sebelum 4,5 jam untuk mengurangi risiko kematian dan kecacatan. Pasien serangan stroke dapat mengalami gangguan fungsi otak yang disebabkan oleh adanya kerusakan atau kematian jaringan otak. Terlambatnya penanganan stroke pada pasien dapat menyebabkan kerusakan otak yang muncul semakin berat. Intervensi prehospital dapat menjadi upaya awal yang penting dilakukan untuk pasien stroke baik saat pasien masih di rumah atau saat proses transfer ke rumah sakit. Tinjauan pustaka ini bertujuan untuk mengetahui konsep dan penerapan intervensi prehospital yang dapat diberikan kepada pasien stroke. Penelitian ini berupa tinjauan pustaka menggunakan database Pubmed dan search engine google scholar. Kata kunci bahasa Inggris yang digunakan adalah “stroke AND prehospital intervention OR emergency medical services OR EMS”. Sedangkan, kata kunci Bahasa Indonesia yang digunakan adalah “stroke AND intervensi prehospital OR emergency medical services OR EMS”. Hasil didapatkan terdapat 19 artikel full-text yang membahas mengenai intervensi prehospital stroke dengan tahun publikasi 2012-2022. Kesimpulannya, aspek prehospital stroke di Indonesia masih perlu pengembangan dari segi sumber daya manusia maupun infrastrukturnya agar dapat memberikan pelayanan yang optimal bagi pasien yang mengalami serangan stroke. Kata Kunci: Emergency Medical Services, Mobile Stroke Unit, Prehospital, Stroke